Corneal hysteresis and primary open angle glaucoma - Dana, Dascalescu (Rom J Ophthalmol, 2015)
Objects: To investigate the variability of the corneal hysteresis in primary open angle glaucoma(POAG) patients. Material and Methods: Out of 123 eyes, 99 carried out the inclusion criteria and were investigated further using Goldman Aplanotonometer to measure intraocular pressure(IOP), Ocular Response Analyzer(ORA) in order to determine corneal hysteresis (CH) and corneal resistance factor(CRF), ultrasonic pachimetry (Ocuscan) to measure central corneal thickness(CCT) and Humphrey visual field to determine mean deviation(MD), pattern standard deviation(PSD) and visual field index(VFI). The patients were divided into two groups: one group of diagnosed POAG patients and one control group of healthy individuals. Statistical analysis was performed using descriptive analyses and linear regression. Results: A considerable statistic correlation was found between CH and VFI both in the group of primary open angle glaucoma patients(r=0.52, P<0.0001), and the control group (r=0.22, p<0.04). Conclusions: The study shows a positive correlation, statistically significant, between corneal hysteresis and visual field index both in glaucoma patients and control subjects proving that a lower CH associates with a lower VFI. Ocular response analyzer can be considered a useful instrument in evaluation of primary open angle glaucoma patients.